Effects Induced In Vivo by Exposure to Magnetic Signals Derived From a Healing Technique. Issue 1 (27th March 2020) - Beseme, Sarah; Fast, Loren; Bengston, William; Turner, Michael; Radin, Dean; McMichael, John
Energy healing is a therapy said to manipulate and balance the flow of "energies" in the body. One such technique, the Bengston Healing Method (BHM), has shown some success in healing malignant tumors in animals and humans, but the mechanism of action and factors influencing therapeutic success of this method are poorly understood. In this study, we tested in vivo the antitumor potential of magnetic signals recorded during BHM healing. Balb/c mice engrafted with 4T1 breast cancer cells were exposed to this recording for 4 h/d on a weekly or daily basis for 28 days; control mice were not exposed at all. Tumors showed a trend to grow slower in the treatment versus control group during the fourth week of treatment. Elevated leukocyte counts, associated with an increase in blood levels of granulocyte–macrophage colony stimulating factor and interleukin-6, were observed in tumor-bearing mice exposed to the BHM recording but not in healthy animals exposed to the recording. This suggests that exposure to a recording of BHM may induce a biological response in tumor-bearing mice, but limited effects on tumor growth when observed within the predefined end point of 28 days. Studies involving longer end points are recommended to observe the progression of tumor growth.